Dealing with schizophrenia in general practice - N. Khamker (South African Family Practice)
Schizophrenia is a psychiatric illness of unknown aetiology, and impairs cognition and social and occupational functioning. It is challenging in terms of the disability it causes, the unclear nature of what causes it, the complexity of diagnosis and treatment limitations. General practitioners can play a role in various phases of the illness, from early intervention to chronic care, in liaison with the psychiatrist.